Synthesis of a novel mitochondrial fluorescent probe - killing cancer cells in vitro and in vivo - Yang, Xiaowen; Zhan, Yiting; Li, Yifei; Shen, Xinzhuang; Ma, Yuqiu; Liu, Zongjun; Liu, Yipeng; Liang, Chengjin; Zhang, Xiaoyuan; Yan, Yehao; Shen, Wenzhi (Frontiers in Pharmacology, 2025)
PurposeThe global incidence and mortality rates associated with cancer are increasing annually, presenting significant challenges in oncology, particularly regarding the efficacy and toxicity of antineoplastic agents. Additionally, mitochondria are recognized for their multifaceted roles in the progression of malignant tumors. Mitochondrial-targeting drugs offer promising avenues for cancer therapy. This study focuses on the synthesis of a mitochondrial fluorescent probe, designated Mitochondrial Probe Molecule-1 (MPM-1), and evaluates its anti-tumor effects on colon cancer (CRC) and lung cancer (LUNG) both in vitro and in vivo.MethodsMito Tracker Green FM staining was performed to investigate the subcellular location of MPM-1. Cell cycle assay, colony formation, EdU, assay of cell apoptosis, wound healing assay, and trans-well migration assay were utilized to confirm anticancer properties of MPM-1 in vitro. Using a xenograft mouse model, the effects of MPM-1 in tumor treatment were also identified. RNA-seq and Western blot were performed to examine the underlying mechanism of MPM-1.ResultsThe findings indicate that MPM-1 selectively targets mitochondria and exerts inhibitory effects on CRC and LUNG cells. Specifically, MPM-1 significantly reduced the proliferation and migration of lung cancer cell lines A549 and H1299, as well as colon cancer cell lines SW480 and LOVO, with IC50 values of 4.900, 7.376, 8.677, and 7.720 µM, respectively, while also promoting apoptosis. RNA-seq analysis revealed that MPM-1 exerts its broad-spectrum anticancer effects through interactions with multiple signaling pathways, including mTOR, Wnt, Hippo, PI3K/Akt, and MAPK pathways. Additionally, in vivo studies demonstrated that MPM-1 effectively inhibited tumor progression.ConclusionIn summary, MPM-1 demonstrates the ability to inhibit the growth of CRC and LUNG by targeting mitochondria and modulating several signaling pathways that attenuate tumor cell migration and proliferation while promoting apoptosis. This research underscores the potential of MPM-1 as a tumor suppressor and lays a robust foundation for the future development of innovative anticancer therapies that target mitochondrial functions.